СИНЕСТЕЗИЯ В КУЛИНАРНОМ БЛОГЕ КАК ПРОЯВЛЕНИЕ ЯЗЫКОВОЙ КРЕАТИВНОСТИ - Łuczyk, Małgorzata (Acta Neophilologica, 2018)
This article attempts to analyze synesthesia in the culinary idiomatic discourse presented in Alexei Oniegin’s blog “Culinary Notes”. In the language employed in the blog synesthesia constitutes one of the author’s creative efforts, which involve the selection of appropriate language means, aiming to give it characteristics of difference, unconventionality and originality.